2013
DOI: 10.5433/1679-0359.2013v34n3p1411-1420
|View full text |Cite
|
Sign up to set email alerts
|

Digestibility of nutrients and energy of cultivars of forage palm for growing Nile tilapia

Abstract: The objective was to evaluate the apparent digestibility coefficients of nutrients and energy of five cultivars of forage palm (orelha de onça, miúda, gigante, IPA 20 and comum) for growing Nile tilapia (110.02±16.17 g). The study design was completely randomized with five treatments, three replicates of eight fish per experimental unit. The diets were composed of 300 g/kg of each cultivar of the palm and 700 g/kg of the basal diet. Masculinized fish were distributed in circular feed tanks (150 L) and kept in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…Miúda presented the lowest ADCCP (26.77%) as well as Orelha de onça (56.07%) and Gigante (55.12%). Oliveira et al (2013) observed a similar result, in which the digestibility of forage palm cultivars was evaluated with Nile tilapia (110 g), finding the highest ADCCP for IPA 20 (75.43%) and Comum (78.21%) cultivars. Braga et al (2010), when analyzing the digestibility of mesquite pod flour, cassava leaf, and cocoa bran with juvenile tilapia, found ADCDM values of 48.7%, 50.2%, and 43.9%, ADCCP values of 51.6%, 49.8, and 38.5%, and ADCCE values of 30.5%, 29.3%, and 23.1%, respectively.…”
Section: Digestibilitysupporting
confidence: 60%
See 1 more Smart Citation
“…Miúda presented the lowest ADCCP (26.77%) as well as Orelha de onça (56.07%) and Gigante (55.12%). Oliveira et al (2013) observed a similar result, in which the digestibility of forage palm cultivars was evaluated with Nile tilapia (110 g), finding the highest ADCCP for IPA 20 (75.43%) and Comum (78.21%) cultivars. Braga et al (2010), when analyzing the digestibility of mesquite pod flour, cassava leaf, and cocoa bran with juvenile tilapia, found ADCDM values of 48.7%, 50.2%, and 43.9%, ADCCP values of 51.6%, 49.8, and 38.5%, and ADCCE values of 30.5%, 29.3%, and 23.1%, respectively.…”
Section: Digestibilitysupporting
confidence: 60%
“…The Miúda cultivar presented the smallest ADCDM (17.04%), presenting no differences compared to Comum. Oliveira et al (2013), when working with Nile tilapia (around 110 g), found superior ADCDM with all palm cultivars tested, i.e. the cultivars Orelha de onça, Comum, Gigante, IPA 20, and Miúda at 54%, 53%, 50%, 48.3%, and 47.9%, respectively.…”
Section: Digestibilitymentioning
confidence: 92%
“…In the lower part of the aquariums there was a tap equipped with a collector, which was later immersed in ice in a Styrofoam box for stool collection, according to the methodology proposed by Oliveira et al (2013). The temperature, pH and dissolved oxygen content of the water were monitored daily with a YSI Professional Plus multiparameter apparatus (YSI Incorporated, Yellow Springs, OH, USA), and over the course of the experiment, the average values were 25.75 ± 0.8ºC, 7.49 ± 0.3 pH and 8.25 ± 1.2 mg/L, respectively.…”
Section: Methodsmentioning
confidence: 99%